2002
DOI: 10.4319/lo.2002.47.1.0278
|View full text |Cite
|
Sign up to set email alerts
|

Landscape variation in phosphorus concentration and effects on detritus‐based tropical streams

Abstract: Landscape-scale variation in streamwater phosphorus (P) concentration can affect aquatic food webs. Such variation occurs naturally in streams at La Selva Biological Station in Costa Rica due to spatially variable inputs of geothermally modified groundwater. We examined effects of this gradient on detrital food web components at 16 stream sites. The Michaelis-Menten model provided a good fit of the relationship between soluble reactive phosphorus (SRP) and leaf decay rate, fungal biomass, and invertebrate biom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
138
4
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 137 publications
(157 citation statements)
references
References 49 publications
14
138
4
1
Order By: Relevance
“…Total N was higher during the Hong Kong dry season, when PO 4 also showed a non-significant increase, but their potential effects were overwhelmed by effects of seasonal variation in temperature and discharge. Nonetheless, PO 4 concentration during the dry season (range = 2.6-6.4 lg l -1 ) was one of the important predictors of breakdown rates, as has been reported in previous studies in Hong Kong , presumably due to enhancement of microbial (fungal and bacteria) activity (Rosemond et al, 2002).…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…Total N was higher during the Hong Kong dry season, when PO 4 also showed a non-significant increase, but their potential effects were overwhelmed by effects of seasonal variation in temperature and discharge. Nonetheless, PO 4 concentration during the dry season (range = 2.6-6.4 lg l -1 ) was one of the important predictors of breakdown rates, as has been reported in previous studies in Hong Kong , presumably due to enhancement of microbial (fungal and bacteria) activity (Rosemond et al, 2002).…”
Section: Discussionsupporting
confidence: 68%
“…Litter breakdown rate are often positively correlated with nutrient loads (e.g. Suberkropp & Chauvet, 1995;Rosemond et al, 2002). Total N was higher during the Hong Kong dry season, when PO 4 also showed a non-significant increase, but their potential effects were overwhelmed by effects of seasonal variation in temperature and discharge.…”
Section: Discussionmentioning
confidence: 99%
“…Although a number of studies have demonstrated a causal link between nutrient enrichment and increased microbial activity, detrital quality, and decomposition rates, few studies have examined the consequences of these basal changes on the growth and production of detritivorous macroconsumers (but see Rosemond et al 2002). In this study, we observed marked differences between the response of chironomids and Tallaperla spp.…”
Section: Discussionmentioning
confidence: 52%
“…In detritus-based stream ecosystems, nutrient enrichment is capable of stimulating microbial biomass and activity (e.g., Ramírez et al 2003;Stelzer et al 2003), invertebrate biomass and production (e.g., Pearson and Connolly 2000;Rosemond et al 2002;Cross 2004), and leaf litter decomposition (e.g., Elwood et al 1981;Gulis and Suberkropp 2003). During a sufficient time period, these factors may lead to a net loss of carbon from the system (Rosemond unpubl.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation